2016
DOI: 10.1371/journal.pone.0157922
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Gas Plasma Generated by a Static Induction Thyristor as a Pulsed Power Supply Inactivates Adenovirus

Abstract: Adenovirus is one of the most important causative agents of iatrogenic infections derived from contaminated medical devices or finger contact. In this study, we investigated whether nitrogen gas plasma, generated by applying a short high-voltage pulse to nitrogen using a static induction thyristor power supply (1.5 kilo pulse per second), exhibited a virucidal effect against adenoviruses. Viral titer was reduced by one log within 0.94 min. Results from detection of viral capsid proteins, hexon and penton, by W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
3
35
1
Order By: Relevance
“…The oxidative stress analysis of CAP on the capsid of FCV agrees with the results of Wigginton et al [ 22 ] on the impact of ozone (one of identified CAP species in our system) on binding of bacteriophage F2 to its host cells. However, our results are contrary to those obtained by Sakudo et al [ 14 ] who found that no alteration in capsid protein of an adenovirus by the species of CAP. This might be due to the differences between structures of adenoviruses and caliciviruses and/or the difference between the CAP species generated by their and our plasma setups.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The oxidative stress analysis of CAP on the capsid of FCV agrees with the results of Wigginton et al [ 22 ] on the impact of ozone (one of identified CAP species in our system) on binding of bacteriophage F2 to its host cells. However, our results are contrary to those obtained by Sakudo et al [ 14 ] who found that no alteration in capsid protein of an adenovirus by the species of CAP. This might be due to the differences between structures of adenoviruses and caliciviruses and/or the difference between the CAP species generated by their and our plasma setups.…”
Section: Resultscontrasting
confidence: 99%
“…However, Yasuda et al [ 18 ] reported results, which suggest that the inactivation of bacteriophage lambda by cold plasma was mainly due to oxidation of the coat protein, and to a lesser extent, by damage to the DNA. A similar mode of action of CAP on bacteriophage MS2 [ 19 ] and human adenovirus [ 20 ], has been suggested but Sakudo et al [ 14 ] found that the reactive chemical species of nitrogen plasma inactivated an adenovirus by damaging its genomic DNA without any alteration in its capsid protein, hexon, or penton [ 14 ]. Similarly, ultraviolet light inactivates viruses by damaging their nucleic acids [ 21 ].…”
Section: Introductionmentioning
confidence: 90%
“…Researchers also use CAPs successfully inactivate various virus and mechanism has been investigated as well [49][50][51].…”
Section: Plasma Interaction With Microorganismsmentioning
confidence: 99%
“…Recently, a nitrogen gas plasma instrument (BLP-TES), which generates nitrogen gas plasma using a fast high-voltage pulse from a static induction (SI) thyristor power supply was developed (5)(6)(7)(8)(9)(10)(11). Our previous studies (5)(6)(7)(8)(9)(10)(11) have demonstrated that nitrogen gas plasma can be utilized to inactivate various microorganisms. However, the mechanisms of action of gas plasma on microorganisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that nitrogen gas plasma treatment using BLP-TES efficiently inactivates bacteria and viruses as well as endotoxins (5)(6)(7)(8)(9)(10)(11). Furthermore, Geobacillus stearothermophilus, which is often used as a biological indicator for gas plasma and is one of the most resistant microbes against physical and chemical treatments, was inactivated by treatment with BLP-TES (6,12).…”
Section: Introductionmentioning
confidence: 99%